2021
DOI: 10.2319/060920-531.1
|View full text |Cite
|
Sign up to set email alerts
|

FGF10andFGF13genetic variation and tooth-size discrepancies

Abstract: Objectives To explore whether variations in odontogenesis-related genes are associated with tooth-size discrepancies. Materials and Methods Measurements of the width of permanent teeth were obtained from dental casts of 62 orthodontic patients (age 15.65 ± 6.82 years; 29 males and 33 females). Participants were classified according to the anterior and overall Bolton ratios as without tooth-size discrepancy or with maxillary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Our data of reduced dental crown size in FGF10 +/− mutant mice is consistent with observations made in craniosynostosis and LADD syndromes 36–38 . Another FGF10 ‘single nucleotide polymorphisms’ mutation has also been linked to macrodontia, 39 and, although these polymorphisms are not directly related to our study, the collective observations reiterate the notion that the FGF10 gene is an important regulator of tooth size. The underlying mechanism of the dental developmental anomaly is likely to involve disrupted FGF10 function in the epithelial‐mesenchymal interactions (reciprocal signalling) during amelogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…Our data of reduced dental crown size in FGF10 +/− mutant mice is consistent with observations made in craniosynostosis and LADD syndromes 36–38 . Another FGF10 ‘single nucleotide polymorphisms’ mutation has also been linked to macrodontia, 39 and, although these polymorphisms are not directly related to our study, the collective observations reiterate the notion that the FGF10 gene is an important regulator of tooth size. The underlying mechanism of the dental developmental anomaly is likely to involve disrupted FGF10 function in the epithelial‐mesenchymal interactions (reciprocal signalling) during amelogenesis.…”
Section: Discussionsupporting
confidence: 92%
“…Studies indicate that the morphogenesis of each type of tooth is differently regulated by different growth factors [30][31][32]. Thus, it is reasonable to hypothesize that testosterone suppression may affect a specific type or group of teeth [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that the morphogenesis of each type of tooth is regulated by different growth factors and different sets of genes. 6,8,12 Therefore, it is reasonable to suggest that SNPs in growth factor decoder genes can influence the tooth size of only one type, one arch or one group of teeth, and impact the occlusal relationship, [13][14][15] depending on the group of genotypes and alleles that the patient carries. The investigated SNPs in BMP2 and BMP4 were not associated with tooth-size excess in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a previous history of orthodontic treatment, congenital syndromes, tooth anomalies, interproximal caries, restorations or enamel reduction, occlusal dental wear, fractured or poorquality dental casts, and extreme tooth misalignment, were excluded. The sample was previously described by Marañón-Vásquez et al 13 Sixty-two patients were included in the current study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation